Smooth functions on 2-torus whose Kronrod-Reeb graph contains a cycle - Maksymenko, S.; Feshchenko, B. (Methods of Functional Analysis and Topology, 2015)
Let f:M→ R be a Morse function on a connected compact surface M, and S(f) and O(f) be respectively the stabilizer and the orbit of f with respect to the right action of the group of diffeomorphisms D(M). In a series of papers the first author described the homotopy types of connected components of S(f) and O(f) for the cases when M is either a 2-disk or a cylinder or χ(M)